LEGAL PROTECTION FOR HUMAN TRAFFICKING: A Case Study of Sidoarjo District Court Decision No. 889/PID.SUS/2018/PN.SDA - Rahmawati, Shofi Nurul; Sumaryanto, Djoko (jfpublisher, 2022)
The objective of this research is to determine the regulation of the human trafficking crime and analyze of the human trafficking crime in Decision No. 889/PID.SUS/2018/PN.SDA. A criminal act or